Terapi kerokan efektif meningkatkan status hemodinamik pada pasien hipertensi - Adi Sucipto; Siti Fadlilah (MEDIA ILMU KESEHATAN, 2023)
Background: The number of hypertensive patients is increasing and is one of the highest causes of death. Non-pharmacotherapeutic treatment of hypertension can use complementary therapies, one of which is scraping therapy. Objective: Aim of the study was to determine the effect of scraping therapy on pulse and blood pressure in hypertensive patients. Methods: This method was a quasi-experimental study with pretest and posttest control group design. The sample consisted of control and intervention groups, each of which was 40 people taken by consecutive sampling. Results: The control group experienced an increase in pulse, systolic and diastolic (1.05 beats/minute and 1.00 mmHg, 1.775 mmHg), the intervention group experienced a decrease in pulse, systolic and diastolic (1,525 beats/minute; 7.70 mmHg; and 5, 05 mm Hg). The control group bivariate test on pulse, systolic, and diastolic variables showed p=0.113; p=0.748; and p=0.267. Bivariate test of intervention group on pulse, systolic, and diastolic variables showed p=0.0035; p<0.001; and p<0.001. Different test of pulse, systolic, and diastolic variables showed p=0.001; p<0.001; and p<0.001. Conclusion: Scraping therapy is effective in reducing pulse and blood pressure of hypertensive patients so that it can be used as an inexpensive alternative therapy option.